Modified Coronally Positioned Flap for Isolated Gingival Recession, Evaluated with Root Coverage Esthetic Score System - Giri, Dhirendra Kumar; Yadav, Ajit Kumar (Journal of Nobel Medical College, 2021)
Background: Various modifications of the coronally displaced flap have been proposed in the literature with the attempt of treating gingival recession. This study is undertaken to evaluate the predictability of the modified coronally positioned flap in isolated gingival recession not only in terms of root coverage but also with the esthetic outcome.Materials and Methods: Fifteen isolated gingival recessions with at least 1mm of keratinized tissue apical to the defect were treated with a modified coronally advanced flap. All recessions fall into Miller class I. The clinical re-evaluation was performed 3 months and 1year after the surgery. Statistical analysis was performed using statistical application software (SPSS16.0). Multivariate ANOVA was used for analysis.Results: At the 1-year examination, the average root coverage was 94.6% of the pre-operative recession depth. There was a mean clinical attachment gain of 3.3±0.1 mm at 1 year follow-up.The average increase of keratinized tissue between the baseline and the 1-year follow-up amounted to 1.53±0.13 mm. Root coverage esthetic score (RES) was recorded at the end of follow-up period. 13/15 cases showed RES score of 9 and 2/15 cases showed RES score of 6.Conclusion: The modified coronally advanced surgical technique is effective in the treatment of isolated gingival recession in the upper jaw.